ANALISIS NILAI-NILAI PEMBELAJARAN BERMAKNA (MEANINGFUL LEARNING) DALAM KITAB AL-AJRUMIYYAH UNTUK MENINGKATKAN KUALITAS PENDIDIKAN BAHASA ARAB - Widia Yelsa; Fatmawati; Putri Dewi Aulia; Marlina; Nurdiana; Mahyudin Ritonga (Didaktik : Jurnal Ilmiah PGSD STKIP Subang, 2026)
This study aims to deconstruct and conduct an in-depth analysis of the pedagogical structure of the classical text Al-Ajrumiyyah through the lens of David Ausubel’s Meaningful Learning theory. In the context of Arabic language education in Indonesia, the primary challenges are low knowledge retention and the failure to functionally apply grammatical rules in real communication issues often stemming from the dominance of rote learning methods. Utilizing a library research approach with content analysis techniques, this study explores how the systematics of the 25 chapters in Al-Ajrumiyyah reflect cognitive principles such as advance organizers, progressive differentiation, integrative reconciliation, and subsumption. The results indicate that this text is not merely a grammatical summary, but a cognitive instrument deductively structured to facilitate the stable assimilation of new information into the student's existing knowledge structure.These findings suggest that integrating meaningful learning values into the teaching of Kitab Kuning can transform the effectiveness of Arabic education, address student heterogeneity, and align Pesantren traditions with modern curricular demands. The implications of this research emphasize the need for a methodological reorientation among Arabic educators to prioritize conceptual interconnectedness over the mere accumulation of verbal information